Monitoring the quality of essential oil from etilingera SP.4 (Zingiberaceae) by gas chromatography-mass spectrometry (GC-MS) - Chua, Share Kung (2008)
Essential oils are volatile, fragrant oils that occur in plants and in general contribute to their characteristic odors, flavors, or other properties. Studies have revealed that there is a spectrum of essential oils present in Zingibereaceae species, which are used widely as spice, flavouring and medicinal sources. The focus of current research was given to a wild species named as sp.4 from the genus Etlingera whose most species are still in undeveloped stage. The extraction of essential oil from the rhizome material of Etlingera sp.4 was conducted by hydro-distillation process using an all glass Clevenger-type apparatus. The compositions of essential oil isolated were further analyzed by gas chromatography-mass spectrometry (GC-MS) analysis. In addition, the effects of storage conditions including exposure to heat and light on the quality of essential oil were observed for 3 weeks. The changes in the compositions of essential oil were monitored by comparing the area of peaks. Based on the quantitative analysis of the GC-MS results, it was discovered that extreme storage conditions will result in the loss of certain volatile oil components in essential oils. Thus, optimum storage condition must be applied on natural essential oil to preserve its freshness and potency.